Peran Teacher Support terhadap Student Engagement melalui Basic Needs Satisfaction pada Siswa SMA - Jane Savitri; Meilani Rohinsa; Serena Wijaya; Stephanie Andamari; Meilia Trisito Anggraeni (Humanitas (Jurnal Psikologi), 2023)
Research shows that teacher support can increase student involvement in school activities or what is known as school engagement. Students who are engaged are better able to adapt and show better academic achievement. Teachers as authority figures in schools play a role in providing the support that students need. Forms of support that teachers can provide to students include teacher involvement, teacher autonomy support and teacher structure. How teacher support influences high school students' school engagement will be seen based on the Basic Needs Satisfaction theoretical framework, namely through fulfilling students' basic psychological needs in the form of fulfilling the need for competence, need for autonomy and need for relatedness. Data were collected using the Teacher Support questionnaire which was constructed by researchers based on the theory of Klem and Connell (2004), the Basic Needs Satisfaction questionnaire was an adaptation of the "Feeling I Have" measuring instrument constructed by Deci and Ryan (2000), while the School Engagement questionnaire was constructed by researchers based on the theory of Fredricks, Blumenfeld and Paris (2004). Data processing was carried out using Mediation Analysis. The results of data processing show that Teacher Support can increase student School Engagement directly or indirectly through the three types of Basic Needs Satisfaction (partial mediation). This research provides implications for schools to focus more on developing teachers' abilities in providing involvement, autonomy and structure support.